Edukasi Para Ibu dalam Upaya Pencegahan Stunting pada Daerah Pedesaan di Indonesia Timur - Hiskya, Hendra Jondry; Ronald, Ronald; Lewar, Emanuel (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The urgent problem is that it turns out that there are mothers in Wasur village who have not received education about stunting so that their children do not grow well. many factors including socio-economics, nutritional intake of pregnant women and babies, infections, maternal nutritional status, infectious diseases, micronutrient deficiencies and the environment. This problem must be resolved because it concerns regional and national interests in overcoming the stunting problem in Indonesia. The aim of Community Based Service activities is to provide education to prevent and reduce the number of stunting incidents in Wasur village, Merauke Regency, South Papua Province, which borders directly with Papua New Guinea. The number of participants was 50 people. The methods implemented in this service are 1) preparation, 2) introduction, 3) Socialization, and 4) Mentoring. Participants in the service are Papuan mothers in Wasur village. The evaluation was carried out in the form of distributing questionnaires to participants to determine their level of understanding of the stunting material provided. From the evaluation results, there was an increase in the knowledge of Papuan mothers by a percentage of 26.9%. From these results it can be said that there has been a good increase in Papuan mothers' understanding of stunting.